Pharmacological blockade of TRPA1 inhibits mechanical firing in nociceptors - Moran Magdalene M; del Camino Donato; Kerstein Patrick C; Stucky Cheryl L (SAGE Publishing, 2009)
Abstract Background TRPA1 has been implicated in both chemo- and mechanosensation. Recent work demonstrates that inhibiting TRPA1 function reduces mechanical hypersensitivity produced by inflammation. Furthermore, a broad range of chemical irritants require functional TRPA1 to exert their effects. In this study we use the ex-vivo skin-nerve preparation to directly determine the contribution of TRPA1 to mechanical- and chemical-evoked responses at the level of the primary afferent terminal. Results Acute application of HC-030031, a selective TRPA1 antagonist, inhibited all formalin responses in rat C fibers but had no effect on TRPV1 function, assessed by capsaicin responsiveness. Genetic ablation experiments corroborated the pharmacological findings as C fibers from wild type mice responded to both formalin and capsaicin, but fibers from their TRPA1-deficient littermates responded only to capsaicin. HC-030031 markedly reduced the mechanically-evoked action potential firing in rat and wild type mouse C fibers, particularly at high-intensity forces, but had no effect on the mechanical responsiveness of Aδ fiber nociceptors. Furthermore, HC-030031 had no effect on mechanically-evoked firing in C fibers from TRPA1-deficient mice, indicating that HC-030031 inhibits mechanically-evoked firing via a TRPA1-dependent mechanism. Conclusion Our data show that acute pharmacological blockade of TRPA1 at the cutaneous receptive field inhibits formalin-evoked activation and markedly reduces mechanically-evoked action potential firing in C fibers. Thus, functional TRPA1 at sensory afferent terminals in skin is required for their responsiveness to both noxious chemical and mechanical stimuli.